(3jHOh Cfg JfHjg GdZGadjf ddSeQbfOjs - (3eLghds ((3SdjeGf Hf QeVGfs)
(3ChdgG (B:s
(3HSe Gddg bjd GdNdb Ydi YTQI CLRGA JSYI efgG ddTjGWjf hGdLf hhGMO efgG ddEfSGf Ke LYd ddEfS eGFI hNeSI hYTQjf UfaG aGdeGAI efgG jCLhL heCLhL hNeS hYTQhf SGFQ GdNdb s
(3BNQgG (B:s
(3cfG LdhSG YfO GdfHj h e hMVQ QLd MSf GdhLg hGdKjGH WjH GdQGFMI dG Ydjg CKQ GdSaQ aSde GdfHj Y e aQO Y e GdSdGe HEYRGR hGdEcQGe abGd Pdc GdQLd CNHQfj Yf GdEjeGf abGd JeJ GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdMOjK hGdeUWdMs